Computer Simulation of Surface Plasmon Resonance for Optical Multi-Layer System - Mohamed Siddig, Mohamed Ahmed (2000)
Surface plasmon is a charge density wave on the surface of metals. The surface plasmon resonance technique is relatively new, and it is one of the most sensitive techniques to probe surface and interface effects. The Fresnel's equations and Snell's law are used to compute the reflection and transmittance of light incident on multilayers (series of N layers and N+ 1 interfaces) between semi-infinite ambient and substrate media. The effects of multiple reflection are taken care of by using 2 x 2 scattering matrix techniques. A plot of a graph for reflectance and transmittance can be obtained by varying the incident angle of a light beam at fixed frequency, or by varying the wavelength. Various plots of reflectance and transmittance as a function of incident angle, wavelength and interface parameters are displayed. The Visual Basic 5.0 standard edition was used in this project whereby a window-based program with graphic user interface (QUI) was developed for the simulation of reflectance and transmittance. After the software program was developed, it was tested with four simulations with well-known experimental results to ascertain the reliability of the simulations. Some of the optical experiments for the both sections of program namely; the reflection and transmission versus incident angle and versus wavelength were simulated. These simulations were studied with Krestchmann's and Otto's configurations. The effect of variation of thickness, dielectric constants, incident angles and wavelengths were demonstrated. Based on the above simulation results, it can be concluded that the program is general enough and it can be used to simulate reflectance and transmittance for any materials.